Device-based therapy for decompensated heart failure: An updated review of devices in development based on the DRI2P2S classification - de Oliveira Cardoso, Cristiano; Elgalad, Abdelmotagaly; Li, Ke; Perin, Emerson C. (Frontiers in Cardiovascular Medicine, 2022)
Congestive heart failure (HF) is a devastating disease leading to prolonged hospitalization, high morbidity and mortality rates, and increased costs. Well-established treatments for decompensated or unstable patients include medications and mechanical cardiac support devices. For acute HF decompensation, new devices are being developed to help relieve symptoms and recover heart and renal function in these patients. A recent device-based classification scheme, collectively classified as DRI2P2S, has been proposed to better describe these new device-based therapies based on their mechanism: dilators (increase venous capacitance), removers (direct removal of sodium and water), inotropes (increase left ventricular contractility), interstitials (accelerate removal of lymph), pushers (increase renal arterial pressure), pullers (decrease renal venous pressure), and selective (selective intrarenal drug infusion). In this review, we describe the new class of medical devices with the most current results reported in preclinical models and clinical trials.